When Whole(ness) is more than the Sum of the Parts: somatics as contemporary epistemological field - Fernandes (Universidade Federal da Bahia, UFBA, Salvador, Brazil), Ciane (Revista Brasileira de Estudos da Presença, 2022)
In the text, it is discussed some aspects on somatics in contemporary times, from the starting point of its technical and conceptual basis, clarifying premises and applications, as well as misunderstandings and restrictions. Some aspects include: conceptual, historical, and technical origins; common premises and principles developed by diverse somatic techniques; the difference between somatic technique, method, and approach; transculturality, decolonization, and repatterning; Somatic Attunement and Wisdom; institutionalization in technical and/or academic courses; somatics as autonomous field of therapy, education, aesthetics, and research; somatics as practice as research; somatic-performative research.